Antiplatelet therapy in the primary prevention of cardiovascular disease in patients with chronic obstructive pulmonary disease: protocol of a randomised controlled proof-of-concept trial (APPLE COPD-ICON 2). Issue 5 (26th May 2018) - Kunadian, Vijay; Chan, Danny; Ali, Hani; Wilkinson, Nina; Howe, Nicola; McColl, Elaine; Thornton, Jared; von Wilamowitz-Moellendorff, Alexander; Holstein, Eva-Maria; Burns, Graham; Fisher, Andrew; Stocken, Deborah; et al.
Abstract : Introduction: The antiplatelet therapy in the primary prevention of cardiovascular disease in patients with chronic obstructive pulmonary disease (APPLE COPD-ICON2) trial is a prospective 2×2 factorial, double-blinded proof-of-concept randomised controlled trial targeting patients with chronic obstructive pulmonary disease (COPD) at high risk of cardiovascular disease. The primary goal of this trial is to investigate if treatment with antiplatelet therapy will produce the required response in platelet function measured using the Multiplate test in patients with COPD. Methods and analysis: Patients with COPD are screened for eligibility using inclusion and exclusion criteria. Eligible patients are randomised and allocated into one of four groups to receive aspirin plus placebo, ticagrelor plus placebo, aspirin plus ticagrelor or placebo only. Markers of systemic inflammation, platelet reactivity, arterial stiffness, carotid intima-media thickness (CIMT), lung function and quality of life questionnaires are assessed. The primary outcome consists of inhibition (binary response) of aspirin and ADP-induced platelet function at 6 months. Secondary outcomes include changes in inflammatory markers, CIMT, non-invasive measures of vascular stiffness, quality of life using questionnaires (EuroQol–five dimensions–five levels of perceived problems (EQ5D-5L), St. George's COPD questionnaire) and to record occurrence of repeat hospitalisation, angina, myocardial infarction or death from baseline to 6 months. Safety outcomes will be rates of major and minor bleeding, forced expiratory volume in 1 s, forced vital capacity and Medical Research Council dyspnoea scale. Ethics and dissemination: The study was approved by the North East-Tyne and Wear South Research Ethics Committee (15/NE/0155). Findings of the study will be presented in scientific sessions and published in peer-reviewed journals. Trial registration number: ISRCTN43245574; Pre-results .